132k views
3 votes
Solve for y in terms of x and replace y with the function notation

Solve for y in terms of x and replace y with the function notation-example-1
User Lumo
by
4.7k points

1 Answer

1 vote

Given:-


y+2x^2=3-2x

To find f(x) and also f(3).

So now to find f(x) we keep y on left hand side and all other terms in right hand side

So we get,


y=3-2x-2x^2=f(x)

So the required solution is,


f(x)=3-2x-2x^2

So now to find the value of f(3). we substitute the value 3 in place of x. so we get,


\begin{gathered} f(x)=3-2x-2x^2 \\ f(3)=3-2*3-2(3)^2 \\ f(3)=3-6-18 \\ f(3)=-3-18 \\ f(3)=-21 \end{gathered}

So the required solution is -21.

User Peter Nguyen
by
4.9k points